Beyond the Borderlands : Migration and Belonging in the United States and Mexico - Lattanzi Shutika, Debra, 1964- (Book collections on Project MUSE., 2011)
Over the last three decades, migration from Mexico to the United States has moved beyond the borderlands to diverse communities across the country, with the most striking transformations in American suburbs and small towns. This study explores the challenges encountered by Mexican families as they endeavor to find their place in the U.S. by focusing on Kennett Square, a small farming village in Pennsylvania known as the "Mushroom Capital of the World." In a highly readable account based on extensive fieldwork among Mexican migrants and their American neighbors, Debra Lattanzi Shutika explores.